Trace element distributions in the Yamato 000593000749,NWA 817 and NWA 998 nakhlites: Implications for their petrogenesis and mantle source on Mars - Wadhwa, Meenakshi; Crozaz, Ghislaine; Barrat, Jean-Alix (National Institute of Polar Research, 2004)
P(論文) We report here results of ion microprobe analyses of rare earth element abundances in various phases in the new Antarctic (paired) nakhlites Yamato 000593 and Yamato 000749, as well as in two additional nakhlites recovered from the Saharan desert, NWA 817 and NWA 998. Although these nakhlites are all composed predominantly of augite and some olivine, they differ from each other, and from the three previously known nakhlites, in the abundance and degree of crystallinity of the interstitial mesostasis. Trace element abundances in various phases in these new nakhlites indicate that they are petrogenetically related to (and comagmatic with) each other and the previously known nakhlites. The calculated parent melt compositions (in equilibrium with augite core compositions) are LREE-enriched and have REE patterns parallel to those of their whole rocks. This suggests that subsequent to accumulation of the olivine and augite, the intercumulus trapped melt evolved in a closed system. The similarity in the estimated parent melt compositions and trace element zonation in the augites of the various nakhlites indicates that these rocks are likely to have formed within a single lithologic unit on Mars. In this scenario, the differences among these nakhlites may be explained in terms of differences in the depth of crystallization within the cumulus pile, represented by different horizons within the same lithologic unit. Based on the partitioning of Eu in their augite cores, the magmatic redox conditions for the nakhlites are estimated to be relatively oxidizing (QFM), implying an oxidized source reservoir in the martian mantle. Late metasomatism of their mantle source by LREE-enriched, oxidizing fluids is suggested to be responsible for the LREE-enrichment and oxidation condition of the nakhlite parent melts. departmental bulletin paper